2012
DOI: 10.2302/kjm.61.66
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Syndrome and Supraventricular Tachycardia Caused by Lavender Tea Toxicity

Abstract: Lavender plants have been used for their cosmetic and biologic benefits for many centries. Extracts from Lavandula plants have been found to cause antimuscarinic effects by blocking sodium and calcium ion channels in in vitro and in vivo studies. We present a case of poisoning by ingestion of tea made from Lavender stoechas ( grass). The patient was admitted to our emergency department with supraventricular tachycardia due to anticholinergic syndrome triggered by drinking lavender tea. On electrocardiography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, the detailed mechanism of lavender action in aromatherapy remains unclear. Several studies have shown it potentially inhibits nausea through anticholinergic, antihistamine and anti-inflammatory activities, and works in conjunction with antiemetic drugs [11]. Aromatherapy works through the principle of relaxation and distraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanism of lavender action in aromatherapy remains unclear. Several studies have shown it potentially inhibits nausea through anticholinergic, antihistamine and anti-inflammatory activities, and works in conjunction with antiemetic drugs [11]. Aromatherapy works through the principle of relaxation and distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Linalool has an effect that is similar to phenobarbital (Elisabetsky, Coelho de Souza, Dos Santos, Siqueira, & Amador, ; Re et al., ). However, caution has been advised in the selection of lavender species because one case report noted that drinking Lavender stoechas (Buckwheat grass) tea triggered anticholinergic syndrome and supraventricular tachycardia (Acikalin et al., ).…”
Section: Lavender and Sleep Depressive Symptoms And Maternal‐infantmentioning
confidence: 99%